KAJIAN POTENSI BUDIDAYA RUMPUT LAUT DI PERAIRAN PULAU BUNYU MELALUI PENDEKATAN HIDRO-OCEANOGRAFI DAN SISTEM INFORMASI GEOGRAFI - Jimmy Cahyadi; Asbar Laga; Mas Apriyan Noor (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2010)
The purpose of this research is to study potential sea weed cultivation at island waters bunyu by hidro-oceanografi and geography information system. Location of this research on marine culture development zone plan waters (RDTR) island bunyu, Regency bulungan, East Kalimantan, where geographically in 3°24'46